2014
DOI: 10.1111/anu.12138
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of fermented Jatropha protein concentrate inLabeo rohitafingerlings

Abstract: Jatroha protein concentrate (JPC) was prepared by iso-electric precipitation method. A 45-day feeding trial was conducted for the nutritional evaluation of JPC and fermented Jatropha protein concentrate (FJPC) in Labeo rohita fingerlings. Seven iso-nitrogenous (340 g kg À1 CP) and iso-energetic (17 MJ kg À1 ) diets such as C (soy protein concentrate ) , T 1 (50 g kg À1 JPC), T 2 (100 g kg À1 JPC), T 3 (200 g kg À1 JPC), T 4 (50 g kg À1 FJPC), T 5 (100 g kg À1 FJPC) and T 6 (200 g kg À1 FJPC) were fed to respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
60
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 31 publications
9
60
2
Order By: Relevance
“…The variation in their results may be due to the levels of ANFs, nonstarch polysaccharide, and or species differences. Literature have shown that varying level of antimetabolites, indigestible carbohydrates, amino acid imbalances and other complexes may contribute to growth depression often observed when plant protein ingredients are fed at higher inclusion levels to fish, rather than pinpointing one single factor as the primary reason for the adverse effects noticed (Mambrini et al, 1999;Francis and Becker, 2001;Schulz et al, 2007;Slawski et al, 2013;Shamna et al, 2015). However, in the present study, no significant variation was observed in the growth performance of the fish fed RPI in replacement for SPI.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The variation in their results may be due to the levels of ANFs, nonstarch polysaccharide, and or species differences. Literature have shown that varying level of antimetabolites, indigestible carbohydrates, amino acid imbalances and other complexes may contribute to growth depression often observed when plant protein ingredients are fed at higher inclusion levels to fish, rather than pinpointing one single factor as the primary reason for the adverse effects noticed (Mambrini et al, 1999;Francis and Becker, 2001;Schulz et al, 2007;Slawski et al, 2013;Shamna et al, 2015). However, in the present study, no significant variation was observed in the growth performance of the fish fed RPI in replacement for SPI.…”
Section: Discussioncontrasting
confidence: 73%
“…This effects were evidence in cyanide-exposed rabbits and common carp (Okolie and Osagie, 1999;Sadati et al, 2013). Shamna et al (2015) also observed an increased level activity of LDH enzymes in Labeo rohita fingerlings fed phorbol esters-containing jatropha protein concentrate. Nevertheless, such effects were not seen in the present study where LDH activity in both the muscle and liver were found to decrease with increasing RPI levels, suggesting that there is no shift in aerobic metabolism and the fish were not under hypoxic condition.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Given this, the use of alternative plant protein is a strategy to increase the sustainability of aquaculture by reducing feed costs as well as by reducing the environmental impact (Shamna et al . ). Many studies have been conducted to evaluate the replacement of FM in practical diets for tilapia with cheap, locally available plant protein sources (Floreto et al .…”
Section: Introductionmentioning
confidence: 97%
“…This toxic component (PEs) cannot be detoxified or inactivated by heat treatment even at higher temperatures (Makkar et al ). However, various detoxification approaches, such as methanol‐alkaline extraction (Makkar and Becker ), treatment with organic solvent (Devappa et al ), and solid‐state fermentation using Bacillus cereus (Saha and Ghosh ) and Aspergillus niger (Shamna et al ), have been used with variable success. Therefore, this study was designed to examine the effects of dietary replacement of SBM with fermented Jatropha kernel meal (FJKM) on the hemato‐biochemical and histopathological parameters in Labeo rohita fingerlings.…”
mentioning
confidence: 99%